The cost-effectiveness of venous-converted acid-base and blood gas status in pulmonary medical departments - Lars Oddershede; Sabrina Storgaard Petersen; Asgerd Krogh Kristensen; et al (Dove Medical Press, 2010)
Lars Oddershede1, Sabrina Storgaard Petersen1, Asgerd Krogh Kristensen2, Jan Freddy Pedersen3, Stephen Edward Rees1, Lars Ehlers41Department of Health Science and Technology, Aalborg University, Aalborg, Denmark; 2Department of Pulmonary Medicine, Aalborg Hospital Section South, Aalborg, Denmark; 3Department of Clinical Biochemistry, Aalborg Hospital Section South, Aalborg, Denmark; 4Health Economics and Management, Aalborg University, Aalborg, DenmarkIntroduction: The current use of arterial punctures, when obtaining arterial blood gas and acid-base status of patients, are associated with a risk of side effects such as pain and hematoma, and a small risk of more severe complications. This analysis investigated the cost-effectiveness of a new method, where less painful venous-converted tests are used as an alternative to arterial punctures.Methods: A cost–utility analysis was conducted from the Danish hospital perspective using a Markov model. The model represents the admission of a typical patient suffering from chronic obstructive pulmonary disease to the Department of Pulmonary Medicine, Aalborg Hospital. Evidence of the effect of the venous-converted tests’ pain reduction was converted into short-term gain in quality-adjusted life years (QALYs), using the Danish EuroQol-5 Dimension value set. A Monte Carlo second order simulation of 10,000 hypothetical patients was conducted for a midsized and a small department.Results: Monte Carlo simulation of the incremental cost-effectiveness ratio (ICER) was dominant for a midsized department, and for a small department the mean was £10,645 per QALY gained. The scatter plot of ICERs revealed that at a willingness-to-pay (WTP) of £30,000 per QALY gained, the venous conversion method is >95% cost-effective in a midsized department and 51% in a small department.Conclusion: It was concluded that the venous conversion method should be applied to hospitals with midsized pulmonary departments, and could be applied to small pulmonary departments if the WTP is sufficient.Keywords: arterial punctures, cost–utility analysis, Markov model, pain, hematoma